INFLUENCE OF SUBSTRATE ANTIHYPOXANT ON THE IMMUNE SYSTEM CONDITION IN VICTIMS WITH SHOCKOGENETIC TRAUMA - D. Sh. Sa’Dulaev; P. A. Dubikaitis; M. E. Malyshev (Вестник хирургии имени И.И. Грекова)
The observation research of victims with severe combined injury was made, the patients were treated by substrate antihypoxant (cytoflavin) in complex of medical care. The authors revealed a decrease of the number of lymphocytes, CD14+ monocytes and growing number of HLA-DR+ monuclear cells. There was noted a significant reduction of the growth of the number of HLA-DR+ monoclear cells and lower lethality rate in case of application of substrate antihypoxants in complex treatment of given patients.